Intrapartum fetal deaths and unexpected neonatal deaths in the Republic of Ireland: 2011 - 2014; a descriptive study - K. McNamara; K. O'Donoghue; R. A. Greene (BMC, 2018)
Abstract Background Intrapartum fetal death, the death of a fetus during labour, is a tragic outcome of pregnancy. The intrapartum death rate of a country is reflective of the care received by mothers and babies in labour and it is through analysing these cases that good aspects of care, as well as areas for improvement can be identified. Investigating unexpected neonatal deaths that may be associated with an intrapartum event is also helpful to fully appraise intrapartum care. This is a descriptive study of intrapartum fetal deaths and unexpected neonatal deaths in Ireland from 2011 to 2014. Methods Anonymised data pertaining to all intrapartum fetal deaths and unexpected neonatal deaths for the study time period was obtained from the national perinatal epidemiology centre. All statistical analyses were conducted using Statistical package for the Social Sciences (SPSS). Results There were 81 intrapartum fetal deaths from 2011 to 2014, and 36 unexpected neonatal deaths from 2012 to 2014. The overall intrapartum death rate was 0.29 per 1000 births and the corrected intrapartum fetal death rate was 0.16 per 1000 births. The overall unexpected neonatal death rate was 0.17 per 1000 live births. Major Congenital Malformation accounted for 36/81 intrapartum deaths, chorioamnionitis for 18/81, and placental abruption accounted for eight babies' deaths. Intrapartum asphyxia accounted for eight of the intrapartum deaths. With respect to the neonatal deaths over half (21/36, 58.3%) of the babies died as a result of hypoxic ischaemic encephalopathy. Information is also reported on both maternal and individual baby demographics. Conclusions This is the first detailed descriptive analysis of intrapartum deaths and unexpected intrapartum event related neonatal deaths in Ireland. The corrected intrapartum fetal death rate was 0.16 per 1000 births. Despite our results being based on the best available national data on intrapartum deaths and unexpected neonatal deaths, we were unable to identify if any of these deaths could have been prevented. A more formal confidential inquiry based system is necessary to fully appraise these cases.